PERCEPTION OF STUDENTS’ PARTICIPATION IN IN-CLASS SPEAKING ACTIVITIES AND SOME INTRINSIC AND EXTRINSIC MOTIVATIONAL FACTORS AFFECTING THEIR PARTICIPATION: A STUDY ON SECOND YEAR MAINSTREAM STUDENTS AT FACULTY OF ENGLISH LANGUAGE TEACHER EDUCATION, ULIS, VNU - Đinh, Thị Thu Trang (2020)
In the light of Communicative Language Teaching and the framework of learner- centered approach, students‟ oral skills and their active participation in class activities have come to take on added importance. However, in the University of Languages and International Studies (ULIS), Faculty of English Language Teacher Education (FELTE), after years of applying the Communicative Language Teaching into practice, it has been noticed that students‟ active oral participation, particularly in observable speaking classes are not prominent. It was due to students‟ misconception on active participation as well as some extrinsic and intrinsic motivational factors, leading to their low engagement in the lessons. Due to the fact that this issue has not been thoroughly investigated so far, this paper attempt to justify and compare the perception of students‟ participation as assessed by students themselves and teachers as well as discover the factors which have an impact on learners‟ participation.